생태계교란식물 도깨비가지의 발생특성과 관리방안 - 이인용(In-Yong Lee); 김승환(Seung-Hwan Kim); 이용호(Yong-Ho Lee); 안재호(Jae-Ho Ahn); 홍선희(Sun-Hee Hong) (Weed & turfgrass science, 2022)
생태계교란식물인 도깨비가지의 주요 서식처는 목초지이다. 그러나 현재는 목초지뿐만 아니라 도로변, 제방, 논둑과밭둑 및 해안사구 등 우리 생활주변에서도 발생되고 있다. 도깨비가지는 6-7월경에 가지꽃과 유사한 보라색 꽃이 피고9월경에 둥근모양의 노란색 열매를 맺는다. 도깨비가지는 종자와 지하경으로 번식한다. 특히 잘려진 뿌리는 0.5 cm만있어도 새로운 개체를 만들어 확산한다. 따라서 무분별한 경운은 도깨비가지의 확산을 초래할 수 있으나, 주기적인 경운(30일 간격으로 3회 이상)으로 지하경 영양분을 고갈시켜 제거하는 방법을 고려할 수 있다. 또 dicamba나 triclopyr-TEA 등이나 glyphosate 등과 같은 제초제 살포로 방제할 수 있다. 한편으로는 도깨비가지를 체계적으로 관리할 수 있는 경종적 방제법과 생물학적 방제법에 대한 연구가 더 필요하다. The main habitat of Solanum carolinense, an ecosystem-disrupting invasive plant in Korea, is known as pasture. However, it is now occurring not only in pastures, but also in roadsides, embankments, paddy and upland levees and coastal sand dunes. The flowers of S. carolinense bloom purple flowers similar to eggplant flowers from June to July, and bear rounded yellow fruits around September. S. carolinense propagates by seeds and underground rhizomes. Roots cut by tillage can be regenerated with 0.5 cm fragments. Therefore, indiscriminate tillage can cause the spread of S. carolinense, but a method of consuming and removing nutrients from rhizomes through periodic tillage (at least 3 times at 30-day intervals) can be considered. It can also be controlled by spraying herbicides such as dicamba, triclopyr-TEA, or glyphosate. On the one hand, the systematic control of S. carolinense requires additional research on cultural and biological control techniques. KCI Citation Count: 0